World monies or money-worlds: A new perspective on cryptocurrencies and their moneyness - Adam Hayes (Finance and Society, 2021)
This essay makes the case that current debates about the 'moneyness' of Bitcoin and other cryptocurrencies are occurring at the incorrect scale. Rather than being some form of trans-national digital money to be used alongside or compete with national fiat currencies, I argue that, instead, each cryptocurrency represents its own self-contained "money-world". Put differently, a cryptocurrency is the uniquely specified unit of account and medium of exchange within the socio-technical bounds of its own blockchain. This new perspective can open new lines of intellectual dialogue and inform better policy choices for regulating cryptocurrencies.
Keywords: 300; Bitcoin; cryptocurrency; money; blockchain